The Influence Of Service Quality Through Patient Satisfaction And Trust Toward Patient Commitment Of RSUD Jayapura Hospital - Setyajidi, Bambang (Advances in Social Sciences Research Journal, 2017)
This study is aimed at building basic and empirical theoretical models, confirming and testing: the effect of service quality on satisfaction, trust, commitment and loyalty. This study was conducted at Jayapura Regional General Hospital. The number of respondents was 294 patients. Measurement of research variables was done by using multiple indicator, then analyzed using structural equation model with AMOS 21 software, and SPSS.Ver.21. The findings of this study are: Service Quality has a positive and significant impact on Patient Satisfaction; Service Quality has a positive and significant effect on Patient Trust; Service Quality has a positive and significant effect on Patient Commitment; Service Quality has a positive and significant effect on Patient Loyalty; Patient Satisfaction has a positive and significant effect on Patient Commitment; Patient Satisfaction has positive and insignificant effect on Patient Loyalty; Patient Trust has positive and insignificant effect on Patient Commitment. In general, the findings of this study provide strong support for the role of commitment required to build long-term relationships and provide strong support for mediation mechanisms.